2008
DOI: 10.1007/s00595-007-3741-z
|View full text |Cite
|
Sign up to set email alerts
|

Horner’s syndrome as a complication of thyroidectomy: Report of a case

Abstract: We report a case of Horner's syndrome (HS) occurring as a complication after total thyroidectomy. Horner's syndrome is characterized by myosis, eyelid ptosis, enophthalmos, and lack of sweating, with vascular dilatation of the lateral part of the face, caused by damage of the cervical sympathetic chain. We found only 28 other reports of HS developing after thyroidectomy, and only seven of these patients recovered completely. Of the 495 thyroidectomies performed at our hospital between 1997 and 2007, only one (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…Data from our present study suggest that tumor location might affect Roux stasis, as demonstrated in patients with tumors in the antrum who appeared to have a higher susceptibility to Roux stasis. Although we could not find direct evidence of a relationship between remnant stomach size and the tumor location, a relatively large remnant stomach has been shown to cause a high incidence of Roux stasis [21,22] and thus a large remnant stomach could affect Roux stasis in patients with tumors in the antrum.…”
Section: Discussionmentioning
confidence: 70%
“…Data from our present study suggest that tumor location might affect Roux stasis, as demonstrated in patients with tumors in the antrum who appeared to have a higher susceptibility to Roux stasis. Although we could not find direct evidence of a relationship between remnant stomach size and the tumor location, a relatively large remnant stomach has been shown to cause a high incidence of Roux stasis [21,22] and thus a large remnant stomach could affect Roux stasis in patients with tumors in the antrum.…”
Section: Discussionmentioning
confidence: 70%
“…Few cases have been reported since, and the majority of cases are associated with conventional thyroidectomy (8). To the best of our knowledge, there have been only 18 cases involving the development of HS as a complication of conventional thyroid surgery since 1993 (Table II) that have been reported in the literature (3,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Due to the development of surgical techniques over the previous two decades, cervical sympathetic damage has also been reported as a post-operative complication that develops subsequent to the completion of open minimally-invasive thyroidectomy and robotic-assisted endoscopic thyroidectomy (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…Although neck surgery is a frequent iatrogenic cause of HS, thyroid surgery-associated HS is rare (3). A previous study reporting the occurrence of HS secondary to thyroidectomy mostly attributed the development of HS to conventional thyroidectomy (4).…”
Section: Introductionmentioning
confidence: 99%
“…Neoplasm of lung apex (Pancoast tumor), vascular injuries, syringohydromyelia, carotid dissection or fibromuscolar dysplasia, are the most common causes [1]. HS has only rarely been reported after thyroidectomy, with only 28 cases mostly published in surgical journals [2,3].…”
mentioning
confidence: 99%
“…The possible causes of HS following thyroidectomy include post-operative hematoma compressing the cervical sympathetic chain, ischemia-induced neural damage caused by lateral ligature on inferior thyroid artery trunk, stretching of the cervical sympathetic chain by the retractor, damage to the anastomosis between the cervical sympathetic chain and the recurrent laryngeal nerve during its identification [2]. Prognosis is usually poor with 70% of patients presenting permanent damage or incomplete recovery.…”
mentioning
confidence: 99%